Manajemen Entrepreneur dalam Meningkatkan Kemandirian Ekonomi Pondok Pesantren Nurul Hidayah Desa Bandung Kecamatan Kebumen - Khasana, Imroh Atul; Soleh, Agus Nur (IAINU Kebumen, 2025)
This study aims to describe entrepreneurial management in enhancing economic independence at Pondok Pesantren Nurul Hidayah, Bandung Village, Kebumen District. The research method employed a qualitative approach with data collection techniques through observation, interviews, and documentation. Data analysis was conducted through data condensation, data presentation, and conclusion drawing. The results showed that entrepreneurial planning at the pesantren was carefully arranged through the determination of business types, activity scheduling, financial planning, and task distribution adjusted to the potential and conditions of the students. Business implementation, such as the production of caps (peci) and tempeh, was able to run sustainably with the integration of religious education and entrepreneurial practice. Supporting factors came from community support and the availability of internal resources within the pesantren, while obstacles included price competition, limited workforce during peak orders, and the influence of external culture on students. Overall, the application of entrepreneurial management at Pondok Pesantren Nurul Hidayah proved effective in improving the economic independence of the pesantren while also providing students with skills to face community life.